2017
DOI: 10.3390/rs9111105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Subpixel Learning Algorithms for Estimating Global Land Cover Fractions from Satellite Data Using High Performance Computing

Abstract: Land cover (LC) refers to the physical and biological cover present over the Earth's surface in terms of the natural environment such as vegetation, water, bare soil, etc. Most LC features occur at finer spatial scales compared to the resolution of primary remote sensing satellites. Therefore, observed data are a mixture of spectral signatures of two or more LC features resulting in mixed pixels. One solution to the mixed pixel problem is the use of subpixel learning algorithms to disintegrate the pixel spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
8
0
4
Order By: Relevance
“…The specific process and implement steps can be found in reference [62]. Subsequently, we applied the FCLS [63], [64] to get the unmixing results, and the expression of FCLS is as follows:…”
Section: Rice Mapping By a Stacked Generalization Approach And Thementioning
confidence: 99%
“…The specific process and implement steps can be found in reference [62]. Subsequently, we applied the FCLS [63], [64] to get the unmixing results, and the expression of FCLS is as follows:…”
Section: Rice Mapping By a Stacked Generalization Approach And Thementioning
confidence: 99%
“…Classification methods applied to salt marshes have been developed for and applied to multiand hyperspectral remote sensing data in a diverse set of biomes worldwide [76][77][78][79][80][81][82]. The large majority of previous approaches to halophytic vegetation mapping determined vegetation abundance by identifying the dominant species in each pixel, using traditional supervised and unsupervised classification algorithms [2,44,76,[83][84][85][86].…”
Section: Introductionmentioning
confidence: 99%
“…Then, we downloaded the pre-and post-forest fire Sentinel 2 data sets and processed them. Second, burned area fraction was derived from the four selected Multispectral Instrument (MSI)/Sentinel 2 bands listed in Table 2 using the FCLS method [44,59,60]. Taking burned area fraction as input for the Modified Pixel Swapping Algorithm (MPSA) in Visual Studio 2012 platform edited by C# language, we obtained the burned area at subpixel level as output.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [41] presented SPA that can provide a general guideline to constrain the total number of endmembers. Kumar et al [44] estimated global land cover fractions from satellite data based on unconstrained lease squares (UCLS), fully constrained least squares (FCLS), modified fully constrained least squares (MFCLS), simplex projection (SP), sparse unmixing via variable splitting and augmented Lagrangian (SUnSAL), SUnSAL and total variation (SUnSAL TV), and Collaborateve SUnSAL (CL SUnSAL), and their results indicated that FCLS outperformed the other techniques. Thus, in this paper, we used FCLS for spectral unmixing of burned area in mixed pixels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation